Some Sources of Misunderstandings in Intercultural Business Communication - Lázár, Tímea (International Journal of Engineering and Management Sciences, 2017)
It is always a big challenge for all types of companies anywhere in the world to survive in the globalised and accelerated world. Their primary objective is to stay competitive, keep or even enlarge their market share while keeping their costs at a minimum level. These corporations often cross borders and operate on a multinational level. In order to do that successfully they need flexible workforce: people who have a high level of intercultural competencies and can help their corporations to achieve their aim of profit maximising. It is widely accepted that culture and languages are among the most significant impacts on intercultural communication. In this paper first I am going to interpret intercultural communication and the role of culture and then look at different intercultural skills and the role of languages in intercultural communication. Some areas that might cause problems in intercultural business communication will also be described.